The Relationship Between Concentration Levels and Strike Outcomes of Woodball Athletes in West Sumatra: CONCENTRATION LEVELS - nurhasanah, rani; nuridin widya pranoto; Hadi Pery Fajri; sonya nelson (Jurnal IKEOR, 2024)
improper hitting direction, a lack of focus and anxiety while striking, striking the ball in the center of the improper rubber cross-section, and instability during the mallet swing, which led the ball to travel off target, were a few of the issues in this research. The purpose of this study is to determine if striking and concentration are related among West Sumatran volleyball players. This study employs the causal social correlation technique and is quantitative in nature. This research involved 30 wooden ball players, and samples were collected for the purpose of selecting a sample, resulting in a total of 25. Grid concentration tests and stroke tests to measure concentration were used. This research was conducted through a survey using measurement and test methods. Data analysis was also carried out using path analysis techniques.